Video: Exploring Colombia's community of practice in food systems - Salas Betancourt, Daniela (2024)
Did you know that there is a Community of Practice in Food Systems in Colombia? That's right! This Community has been operating for a year and serves as a space where entities from different sectors, including universities, international organizations, companies, and public institutions, come together to contribute to the study and construction of solutions to the challenges facing the country's food systems. Throughout its first year of operation, through monthly virtual meetings, the Community of Practice has evolved, adding new members, creating joint projects, and advancing towards clear objectives. On April 3, the first in-person session of 2024 took place, dedicated to the strategic planning of key products to be developed during this year, with the aim of not only studying and filling information gaps about food systems but also generating knowledge products that impact and contribute to informed decision-making.